Hybrid Hash Trees in Blockchain: Evaluating Algorithm Combinations for Speed and Security - V Uday Kumar; Kaila Shahu Chatrapati (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Blockchain technology relies heavily on cryptographic hashing for ensuring data integrity, transaction security, and tamper resistance. However, with increasing data volume and demand for real-time processing, traditional hashing mechanisms often struggle to balance speed and security. This paper proposes and evaluates a novel Hybrid Hash Tree architecture that integrates multiple hash algorithms to optimize both performance and cryptographic strength. By combining the efficiency of lightweight hash functions with the robustness of secure hashing algorithms, the hybrid model aims to accelerate block validation while maintaining high levels of security. Through experimental analysis and performance benchmarking, the study compares various algorithmic combinations to identify optimal configurations suitable for cloud-integrated blockchain environments. The results demonstrate that the proposed hybrid approach significantly enhances transaction speed without compromising security, offering a scalable solution for next-generation blockchain systems.
Keywords: Blockchain; Hybrid; Cryptographic; lightweight